O Riso na Mídia: O Barão de Itararé e seus Almanhaques - os almanaques do jornal A Manha - Aguiar, Odailton Aragão (2006)
Humor was used in different ways throughout mankind s history as a way of relieving differences and difficulties, disintegrating the established power, unmasking imposters, etc. The satyr, caricature, and parody were used in different contexts. Therefore, the jocoseness of the humorist Aparício Torelly, the Baron of Itararé that was one of the Brazilian icons in the field of satiric/critic journalism, was born in this sense. Aparício Torelly brought the laugh and humor to the printed media first in his newspaper A Manha and then in his three Almanhaques that are the satiric version of the traditional almanac. Accordingly, we consider that his work was important to indicate, denounce and even transform the reality because he revealed to the population the truth about the politic power. Consequently, we decided to study the roots of his humor and what existed before his newspaper A Manha. In addition, we investigated the reasons he used the almanac to express his humor; the history of the caricature; the trajectory of Torelly s work; the political framework in which he worked; and the history of Brazilian press, especially the satiric press. We also discussed the way in which modernist Brazilian poets, such as Mário de Andrade and Oswald de Andrade, introduced humor in some of their works as a way of provoking artistic and cultural changes, and how Torelly could be inserted in the same context. To accomplish these aims, we traveled throughout the history of Brazilian printed media and studied how the humor was used in the magazines and newspapers in vogue by the end of the 19th and beginning of the 20th centuries. Analyzing the data gathered during this study, we identified how Torelly s humor was different from that published by others in older magazines. We also highlighted the importance of the almanac as a mass communication vehicle able to transmit information about health, education, etc. We described the elements that Torelly aggregated to delineate his humorousness. We identified the elements that characterize his modern style. Finally, the theoretical support for the research comes from different areas such as the semiotics of culture, studies on humor, caricature, and the history of Brazilian printed media